Murder in the shadows: evidence for an institutional legitimacy theory of crime - Tuttle, James (International journal of comparative and applied criminal justice, 2019)
The focus on the institutional control of violent crime has increased over the past few decades, stimulated largely by Messner and Rosenfeld’s “institutional anomie theory.” A related theory, referred to as “institutional legitimacy theory” in this study, has received considerably less attention. This theory, originating in the social control theoretical tradition, is tested in an analysis of homicide rates (circa 2012) across 108 nations. Overall, institutional legitimacy theory receives support as economic, political, familial, and religious institutional legitimacy assist in reducing homicide rates across societies. Most notably, homicide is positively associated with the size of the shadow economy (the measure of waning economic institutional legitimacy), consistent with the hypothesis that parties lacking institutional redress are more likely to use unilateral violence to resolve grievances.